2009
DOI: 10.1088/0957-4484/20/15/155702
|View full text |Cite
|
Sign up to set email alerts
|

Inter-carbon nanotube contact in thermal transport of controlled-morphology polymer nanocomposites

Abstract: Directional thermal conductivities of aligned carbon nanotube (CNT) polymer nano-composites were calculated using a random walk simulation with and without intercarbon nanotube contact effects. The CNT-contact effect has not been explored for its role in thermal transport, and it is shown here to significantly affect the effective transport properties including anisotropy ratios. The primary focus of the paper is on the non-isotropic heat conduction in aligned-CNT polymeric composites, because this geometry is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…When the number of SWNT bundles is constant, the K eff of the composites decreases as the R CNT−CNT increases. 15,17 A larger R CNT−CNT more significantly impedes the transfer of heat between bundled SWNTs, inducing a lower K eff of the composites. Surprisingly, the heat The Journal of Physical Chemistry C Article transfer mechanism is dominated by a critical SWNT−SWNT TBR, R c , which is estimated to be 0.155 × 10 −8 m 2 K/W.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the number of SWNT bundles is constant, the K eff of the composites decreases as the R CNT−CNT increases. 15,17 A larger R CNT−CNT more significantly impedes the transfer of heat between bundled SWNTs, inducing a lower K eff of the composites. Surprisingly, the heat The Journal of Physical Chemistry C Article transfer mechanism is dominated by a critical SWNT−SWNT TBR, R c , which is estimated to be 0.155 × 10 −8 m 2 K/W.…”
Section: Resultsmentioning
confidence: 99%
“…15 The CNT-CNT TBRs may dominate heat transfer and limit heat conduction in the complex CNTpolymer composites. 2,16 The random walker model developed by Duong et al 15,17 can take into account the CNT bundle configuration and can be used to explore the effect of CNT-CNT TBR in two-phase composites. But prior studies did not investigate the composites with CNT bundles having random orientations and complex morphology (e.g., different number of CNTs in a bundle).…”
Section: Introductionmentioning
confidence: 99%
“…The material properties of these components are given in Table 1 [34] b Calculated from Λ = 3 / by considering = 0.168 Wm -1 K -1 from Reference [20] c Reference [35] d Reference [36] e Calculated from Λ = 3 / by considering = 319 Wm -1 K -1 from Reference [36] f Calculated from experimental correlation given in Reference [37] g Calculated from = 3 / Λ by considering = 37 Wm -1 K -1 from Reference [38] h Interpolation from data at pages 625 and 626 from Reference [38] Note that the values in Table 1 have been obtained in the framework of the so-called "dispersion model" [39] where it is admitted that the phonons have different energies and 13 velocities due to their dispersion. In a previous work [40], we have studied the SiO2-epoxy mixture in absence of agglomeration, i.e.…”
Section: Outlinementioning
confidence: 99%
“…This behavior seems to be less prominent for higher concentrations of particles, when the particle chains begin to merge by side branches (figure 3b shows the scores of the side branches) and the aligned chains gain the transverse contacts between them. The modeling of thermal conductivity of the aligned 1D structure of CNTs along the heat flux showed that creation of the thermal inter-contacts between insulated CNTs leads to decrease of thermal conductivity, for example, it was found reduction of conductivity by ~4 times and ~2 times for the single-walled and the multi-walled CNTs, respectively, at 20 vol.% of aligned CNTs [24]. Hence, sufficient increase of Ni particles content in the composite (higher of 15 vol.%) does not significantly change the initial configuration and therefore the application of magnetic field does not have an important effect on thermal behavior.…”
Section: Thermal Conductivity and Diffusivitymentioning
confidence: 99%
“…The reason is the presence of big amount of filler particles consisting in the dead side branches that cannot be included in 1D structure. Second reason is a closure of these side branches with creation of thermal intercontacts [24] and, as a result, growth of 3D structure over 1D structure with gradual reduction of thermal conductivity at higher Ni concentrations that finally leads to the corresponding of Lichtenecker's model. But evidently the main reason is the contacts between particles and polymer-metal boundaries which scatter the phonons effectively [23].…”
Section: Modelling Of the Effective Thermal Conductivitymentioning
confidence: 99%